Migrant Voices in the Plurilingual Poetry and Creative Practice of Fióna Bolger - Aneta Stępień (ELOPE)
This article investigates the responses of Irish contemporary poetry to transnational migration and the attempts of poets to build empathetic connections with migrants and refugees, who face increasing violence across the European continent and beyond. More specifically, the article examines the centrality of this theme in the work of Fióna Bolger (b. 1972), whose plurilingual poetry and work in the field of creative facilitation demonstrate efforts to connect different cultures, languages and marginalized communities. Bolger’s anti-racism and trauma informed creative practice, discussed in detail in the article, speaks to the power of poetry to create solidarity across various communities and as such may provide a valuable model for artsbased participation in other contexts. The article argues that her work exemplifies decolonial sensibilities (Phipps 2019) that resist the homogenizing views of national literatures as bound by one nation and language, thus escaping narrow understandings of what constitutes Irish and European writing.